Injury incidence in elite youth field hockey players at the 2016 European Championships - Furlong, L.-A. M.; Rolle, U. (PLOS ONE, 2018)
Despite being an essential consideration when deciding rule changes, injury prevention strategies, and athlete development models, there is little epidemiological data of U18 field hockey player injuries-something explicitly referred to in the 2015 International Olympic Committee`s Consensus Statement on Youth Athlete Development. The aim of this study was to quantify incidence and characteristics of injuries in elite youth field hockey players during a major international tournament. Standardized reporting forms detailing time, location on pitch, mechanism and anatomical location of injury were completed for new musculoskeletal conditions resulting in a time stoppage by the umpire and where a player was noticeably affected by an injury for up to 20 s regardless of time stoppage. Injury incidence was 1.35 and 2.20 injuries/match or 53 and 86 injuries per 1000 player match hours for boys (B) and girls (G) respectively; girls were over three times more likely to have a minor injury. Most injuries were contusions due to being hit by the ball or stick (B: 12, G: 27), with high numbers of injuries to the torso (B: 8) and head/face (G: 7). Injuries during the penalty corner (B: 3, G: 4) were to the lower limb and hand, and boys were less likely to wear facial protection (B: 65.9%, G: 86.4%). Results form an essential initial dataset of injuries in U18 field hockey players. Current reporting protocols under-report injuries and must be addressed by the international governing body. The high number of head/face injuries, particularly in females, requires further investigation.